Avaliação da variabilidade da frequência cardíaca em sedentários submetidos ao treinamento resistido e aeróbico - Ramalho, Ellen Sonnaly Vilar (2019)
The regular practice of resistance physical exercise (RE) has been used as a strategy to reduce the risk of cardiovascular diseases, being recommended for both healthy individuals and patients with cardiovascular problems. RE when associated with changes in body composition can improve physical condition and decrease the incidence of overweight, promoting a series of physiological responses resulting from autonomic and hemodynamic adaptations that influence the function of the cardiovascular system. Heart rate variability (HRV) using the frequency domain method is a useful tool for assessing cardiac autonomic balance. In this cross-sectional and longitudinal study, in normotensive, sedentary men (n = 47) and women (n = 51) exposed to resistance (RT) and aerobic (AT) training, the anthropometric parameters [weight, body mass index (BMI)] were investigated.) and percentage of fat, blood glucose, blood pressure and heart rate. At the end of the treatment, the orthostatic tests and the Valsalva maneuver were performed to assess HRV, using the nerve express software. The results showed that the TR and AT can promote reduction of anthropometric parameters in the female group, as well as the reduction of fat percentage in both genders. RT and AT promoted resting bradycardia and reduced basal MAP in both genders. Interestingly, the reduction in MAP after RT was greater in the female group than in the male group. In the evaluation of the autonomic nervous system by HRV, the results showed that TR promoted a significant increase in FH in the female group, without changes in the TA group. In the comparison between the training in the female group, the results showed that the TR promoted a significant increase in the HF in relation to the aerobic training. As for the HRV spectral analysis in valsalva maneuver combined with deep breathing, the TR and TA did not promote significant changes in the HF, LF or LF / HF (ms2) components. Our results suggest that RT, in addition to anthropometric changes, promotes important autonomic changes that influence cardiovascular and metabolic functioning. The results suggest that RT may be indicated for healthy lifestyle as well as for the prevention of cardiometabolic diseases, especially in individuals with family history.